Antimicrobial 'inks' for 3D printing: block copolymer-silver nanoparticle composites synthesised using supercritical CO2. Issue 25 (10th June 2022) - Larder, Ryan R.; Krumins, Eduards; Jacob, Philippa L.; Kortsen, Kristoffer; Cavanagh, Robert; Jiang, Long; Vuotto, Claudia; Francolini, Iolanda; Tuck, Christopher; Taresco, Vincenzo; Howdle, Steven M.
Abstract : A new synthetic methodology to produce polymer-AgNP composite microparticles using scCO2  is presented. These microparticle possessed long-lived antimicrobial activity and were tested for compatibility in the Laser Sintering 3D printing process. Abstract : Silver nanoparticles (AgNP) are widely exploited for their effective antimicrobial activity against a range of pathogens. Their high efficacy in this regard has seen the global demand for AgNP in consumer products steadily increase in recent years, necessitating research into novel low environmental impact synthesis approaches. Here we present a new synthetic methodology to produce polymer-AgNP composite microparticles using supercritical carbon dioxide (scCO2 ) and avoiding use of any petrochemically derived solvents. Poly(methyl methacrylate)-poly(4-vinylpyridine) (PMMA- b -P4VP) block copolymers were synthesised via RAFT-mediated dispersion polymerisation in scCO2, with in situ thermal degradation of various amounts of a CO2 -soluble silver complex. Selective interaction of the silver with the pyridinyl moieties of the block copolymer allowed the formation of AgNP, dispersed within the block copolymer microparticles, leading to homogeneous composites. The by-products of the reaction were also removed by extracting with a flow of CO2 to yield a clean dry product in a single process. The composites were found to be non-cytotoxic and proved to have good antimicrobial activity against two bacterial strains. Though no significant activity was seen for at least the first 24 hours, inhibition of bacterial growth afterwards proved to be extremely persistent, with inhibition observed even after 15 days. Finally, the microparticulate nature of the synthesised composites was exploited and tested for compatibility in the Laser Sintering (LS) 3D printing process. Composite microparticles were fused to produce solid objects, without aggregation of the AgNP. With further optimisation, these composites could prove to be an incredibly versatile 'ink' that may be used within additive manufacturing and 3D printing to rapidly produce bespoke medical devices with inherent antimicrobial activity.